A critical examination of South African law on civil liability for oil pollution damage from ships - Hiscox, Stuart (Faculty of Law, 2021)
Throughout the development of the International Law of the Sea there has been a conflict between the notion of the freedom of the seas and their rights that a coastal state may exercise over the seas adjacent to its territory. This conflict stems from the · coastal state wanting to exploit the resources in the seas as opposed to non-coastal states and other states wanting to exercise the traditional rights, such as the freedom of navigation and fishing, that they enjoyed under the freedom of the seas doctrine. It thus developed that coastal states have certain rights within specified areas of their coasts. These rights extend from complete sovereignty within the internal waters of the state (with the exception that a coastal state cannot refuse entry to a ship in distress) to the exclusive right to exploit minerals found on the continental shelf of the coastal state1 and to exploit the resources in their exclusive economic zone. However, except in regard to internal waters, the other users of the seas still retain some of the rights available to them under the freedom of the seas doctrine, the most important of which is the freedom of navigation. This freedom is not absolute, but it is limited to (innocent passage in the territorial waters, nd it allows vessels not registered in the coastal state to sail within areas that the coastal state and its citizens have rights in. - The question that arises is what is the position if a vessel, not registered in the coastal state, infringes on the rights of the state. In traditional International Law of the Sea the right of recourse lay in the flag state of the vessel and if the flag state did not take any action then the coastal state could not e any punitive measures against the vessel as it did not have jurisdiction over the vessel or her master. It thus developed, alongside the development of the coastal state's rights in regard to the different maritime zones, that specific enforcement jurisdiction was given to the states to preserve the rights that they exercised over those zones.